Induced Ovulation in Catfish Heteropneustes fossilis (Bloch) with Three Native GnRH Peptides - pillai, Devika; Alok, Deoraj; Garg, Lalit C. (Fishery Technology, 2025)
The effect of three native GnRH peptides, viz; salmon GnRH (sGnRH), mammalian GnRH (mGnRH) and chicken GnRH II (cGnRH II), on spawning of the catfish Heteropneustes fossilis (Bloch) was compared. D-Lys6sGnRH, was used as the control. The peptides were synthesized by the Merrifield solid phase method, purified by HPLC and reconstituted in saline. The fish were injected intramuscularly. cGnRH II was more potent than both sGnRH and mGnRH in inducing spawning in this species of catfish. There was no significant difference in the average diameter of the egg obtained using the three peptides.